PC.35 Three year experience of using breast milk fortifier post discharge in preterm babies. (9th June 2014) - King, C
Abstract : Introduction: Preterm babies are often discharged around 35 weeks gestation at a time of rapid growth and immature feeding patterns. This puts them at risk of growth failure. If they are discharged breast feeding they are often given formula top ups to aid growth. An alternative is to continue with some breast milk fortification (BMF); however it is not known whether this may also interfere with breast feeding success. Method: Records of all babies <35 weeks at birth send home on BMF during 2009–2012 inclusive were reviewed and prevalence of any breast feeding at 6 weeks corrected compared with babies sent home breast feeding alone. All babies received iron and vitamins. Results: Of the 32 babies discharged on BMF 63% were still breast feeding at 6 weeks corrected. Of the 120 babies discharged without BMF 45% were still breast feeding. Conclusion: Use of BMF post discharge may help prolong breast feeding in preterm babies, further work is needed to evaluate this intervention.